Amostragem assíncrona baseada em cruzamentos por zero - Santos, Jefferson França (2017)
Synchronous sampling is currently the most widely used analog to digital conversion method, mainly due to its implementation ease, since it employs a constant sampling rate. However, a fixed sampling rate can cause unnecessary activations of the sample and hold circuit, increasing power consumption. Asynchronous analog to digital converters can be used to solve this problem, sampling only when particulars events occur, such as amplitude level crossings. This approach has been intensely studied over the last decades, and arose as an alternative to synchronous sampling. Another asynchronous sampling approach is the one proposed by Voelcker (1966), where sampling instants are the zero crossings of the signal. According to him complex zeros must be sampled for perfect signal reconstruction, in addition to real zeros. Although being physically undetectable, Voelcker proposes that complex zeros can be “transformed” using the real zeros of all nth signal derivatives. Nevertheless this can be unfeasible and this work proposes the use of the Zero Crossing method with a limited number of derivatives. Such approach is justifiable because in consecutive derivatives, real zeros tends to be close or even repeat themselves, thus not aggregating any more information about the original signal. Therefore, this work verifies the applicability of the proposed method for systems that need low power consumption and a good reconstruction of the sampled signal, being suggest from the results of this work as a good solution of compromise between synchronous sampling and Level Crossing.